Ultrasound diagnosis of fetal retroperitoneal lymphangioma with extension to the lower limb - Lacunza Paredes, Rommel Omar (2015)
We report a case lymphangioma in a 30-week gestation fetus, in whom ultrasound examination revealed multiple cystic retroperitoneal images with gluteal extension and involvement of the entire left lower limb; no other associated malformations were found. Diagnosis was confirmed at birth.